The Association Between Vitamin D Levels and Glycemic Control Parameters in Elderly Populations - Gunawan, Shirly; Kosasih, Robert; Wijaya, Bryan Anna; Santoso, Alexander Halim; Firmansyah, Yohanes (Fakultas Kedokteran Universitas Sriwijaya, 2025)
Diabetes is common in the elderly, and routine monitoring of HbA1c and blood glucose is required to prevent complications. HOMA-IR assesses insulin resistance, while vitamin D may influence glucose metabolism by enhancing insulin sensitivity. This study examines the relationship between vitamin D levels and glycemic control, including HbA1c, fasting glucose, insulin, and HOMA-IR. This cross-sectional observational study included 91 elderly residents of Panti Wreda Bina Bhakti, excluding those with acute illness or chronic conditions affecting Vitamin D and diabetes parameters. All participants provided informed consent. The study measured serum Vitamin D-25(OH) and insulin using ELISA, while fasting blood glucose and HbA1c were assessed via blood chemistry analysis. HbA1c control was categorized as good (<6.5%), moderate (6.5–8.0%), or poor (>8%). HOMA-IR was calculated using a standard formula. Pearson correlation analysis determined the relationship between Vitamin D levels and glycemic parameters, with statistical significance at p < 0.05. The correlation analysis found a significant negative relationship between vitamin D levels and HbA1c (r: -0.211; p: 0.044). However, no significant correlation was found between vitamin D and fasting blood glucose levels (r: 0.057; p: 0.590), insulin (r: -0.083; p: 0.432), and HOMA-IR (r: -0.040; p: 0.704). Vitamin D levels show a significant negative correlation with HbA1c in the elderly, indicating its role in long-term glycemic control. Although no significant relationship was found with other glycemic parameters, these findings suggest that monitoring vitamin D status may be considered as part of a more comprehensive approach to diabetes management in the geriatric population.